2018
DOI: 10.3390/mi9110578
|View full text |Cite
|
Sign up to set email alerts
|

Research on a 3-DOF Motion Device Based on the Flexible Mechanism Driven by the Piezoelectric Actuators

Abstract: This paper describes the innovative design of a three-dimensional (3D) motion device based on a flexible mechanism, which is used primarily to produce accurate and fast micro-displacement. For example, the rapid contact and separation of the tool and the workpiece are realized by the operation of the 3D motion device in the machining process. This paper mainly concerns the device performance. A theoretical model for the static performance of the device was established using the matrix-based compliance modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…X out = 6.47X inl X r = 6.17X inl (26) Secondly, the case of driving both of the actuators on the X-axis would be discussed. In this case, equivalent driving forces exist at the output of the bridge-type mechanism on both sides along the X-axis.…”
Section: Fzx Fz1 Fz2mentioning
confidence: 99%
See 1 more Smart Citation
“…X out = 6.47X inl X r = 6.17X inl (26) Secondly, the case of driving both of the actuators on the X-axis would be discussed. In this case, equivalent driving forces exist at the output of the bridge-type mechanism on both sides along the X-axis.…”
Section: Fzx Fz1 Fz2mentioning
confidence: 99%
“…The spatial XYZ-platforms have been widely researched in the past few decades. For example, Lv et al [26] introduced an innovative design based on a three-dimensional (3D) motion device, which can produce precise and fast micro-displacement. Zhu et al [24] adopted the orthogonal arrangement of a three-chain parallel mechanism to achieve the low coupling and high natural frequency of XYZ-axis.…”
Section: Introductionmentioning
confidence: 99%
“…Tung-li Wu et al designed a nanoscale positioning device (6-PSS configure ration) driven by six piezoelectric ceramic actuators mounted directly on the base, which had the advantages of fast response, high stiffness and a small mechanical circuit; the experimental results showed that the device could achieve an 8 μm motion stroke at a resolution of 5 nm, and it can be used to operate equipment with nanoscale motion [ 11 ]. The above studies on the motion of micro-drive systems mainly focused on the amplification motion, and there is less research on micro-drive reduction systems than micro-drive insufficient systems [ 12 , 13 , 14 , 15 ]. A micro-drive reduction system can improve the motion accuracy, increase the scope of application of the micro-drive and provide suitable small-space motion [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 13 ] developed a flexible hinge motion platform with laminated structure based on the limited operators of electron microscope. Lv et al [ 14 ] designed a novel three degrees of freedom (3-DOF) motion device based on flexure hinge, which can realize closed-loop control of large output stiffness. Kim et al [ 15 ] designed a fast tool servo mechanism based on flexure hinge, which is mainly used for diamond turning microstructure manufacturing.…”
Section: Introductionmentioning
confidence: 99%